Trypanosoma cruzi TcSMUG L-surface Mucins Promote Development and Infectivity in the Triatomine Vector Rhodnius prolixus - Gonzalez, Marcelo S. (2013)
Background:TcSMUG L products were recently identified as novel mucin-type glycoconjugates restricted to the surface of insect-dwelling epimastigote forms of Trypanosoma cruzi, the etiological agent of Chagas disease. The remarkable conservation of their predicted mature N-terminal region, which is exposed to the extracellular milieu, suggests that TcSMUG L products may be involved in structural and/or functional aspects of the interaction with the insect vector.Methodology and Principal Findings:Here, we investigated the putative roles of TcSMUG L mucins in both in vivo development and ex vivo attachment of epimastigotes to the luminal surface of the digestive tract of Rhodnius prolixus. Our results indicate that the exogenous addition of TcSMUG L N-terminal peptide, but not control T. cruzi mucin peptides, to the infected bloodmeal inhibited the development of parasites in R. prolixus in a dose-dependent manner. Pre-incubation of insect midguts with the TcSMUG L peptide impaired the ex vivo attachment of epimastigotes to the luminal surface epithelium, likely by competing out TcSMUG L binding sites on the luminal surface of the posterior midgut, as revealed by fluorescence microscopy.Conclusion and Significance:Together, these observations indicate that TcSMUG L mucins are a determinant of both adhesion of T. cruzi epimastigotes to the posterior midgut epithelial cells of the triatomine, and the infection of the insect vector, R. prolixus.